Impact of the updated hemodynamic definitions on diagnosis rates of pulmonary hypertension. (1st August 2020) - Tanyeri, Seda; Akbal, Ozgur Y.; Keskin, Berhan; Hakgor, Aykun; Karagoz, Ali; Tokgoz, Hacer Ceren; Dogan, Cem; Bayram, Zubeyde; Kulahcioglu, Seyhmus; Erdogan, Emrah; Balaban, Ismail; Ceneli, Dogancan; et al.
Abstract : We evaluated whether updated pulmonary hypertension definitive criteria proposed in sixth World Symposium on Pulmonary Hypertension had an impact on diagnosis of overall pulmonary hypertension and pre‐capillary and combined pre‐ and post‐capillary phenotypes as compared to those in European Society of Cardiology/European Respiratory Society 2015 pulmonary hypertension Guidelines. Study group comprised the retrospectively evaluated 1300 patients (age 53.1 ± 18.8 years, female 807, 62.1%) who underwent right heart catheterization with different indications between 2006 and 2018. Mean pulmonary arterial pressure ≥25 mmHg (European Society of Cardiology) and PAMP (mean pulmonary arterial pressure) >20 mmHg (World Symposium on Pulmonary Hypertension) right heart catheterization definitions criteria were used, respectively. For pre‐capillary pulmonary hypertension, pulmonary artery wedge pressure ≤15 mmHg and pulmonary vascular resistance ≥3 Wood units criteria were included in the both definitions. Normal mean pulmonary arterial pressure (<21 mmHg), borderline mean pulmonary arterial pressure elevation (21–24 mmHg), and overt pulmonary hypertension (≥25 mmHg) were documented in 21.1, 9.8, and 69.1% of the patients, respectively. The pre‐capillary and combined pre‐ and post‐capillary pulmonary hypertension were noted in 2.9 and 1.1%, 8.7 and 2.5%, and 34.6 and 36.6% of the patients with normal mean pulmonary arterial pressure, borderline, and overt pulmonary hypertension subgroups, respectively. The World Symposium on Pulmonary Hypertension versus European Society of Cardiology/European Respiratory Society definitions resulted in a net 9.8% increase in the diagnosis of overall pulmonary hypertension whereas increases in the pre‐capillary pulmonary hypertension and combined pre‐ and post‐capillary pulmonary hypertension diagnosis were only 0.8 and 0.3%, respectively. The re‐definition of mean pulmonary arterial pressure threshold seems to increase the frequency of the overall pulmonary hypertension diagnosis. However, this increase was mainly originated from those in post‐capillary pulmonary hypertension subgroup whereas its impact on pre‐capillary and combined pre‐ and post‐capillary pulmonary hypertension was negligible. Moreover, criteria of pre‐capillary pulmonary vascular disease and combined pre‐ and post‐capillary phenotypes were still detectable even in the presence of normal mean pulmonary arterial pressure. The obligatory criteria of pulmonary vascular resistance ≥3 Wood units seems to keep specificity for discrimination between pre‐capillary versus post‐C pulmonary hypertension after lowering the definitive mean pulmonary arterial pressure threshold to 20 mmHg.